Enhancing the lifetime and corrosion resistance of gears made of carbon steel Verbesserung der Lebensdauer und KorrosionsbestÃ¤ndigkeit von ZahnrÃ¤dern aus Kohlenstoffstahl - Ramlee, E.B. (Wiley-VCH Verlag, 2020)
Gears for structural machines require high fatigue strength for high performance. Generally, gears made of carbon steel easily corrode, thus, shortening their fatigue life. The aim of this paper is to improve the fatigue strength of carbon steel gears by means of heat treatment method which was nitriding composed of 95Â nitrogen gas as well as 5Â hydrogen gas, and to investigate its properties after nitriding. Therefore, in order to find the optimum nitriding temperature to increase the hardness and corrosion resistance of gears, the gas nitriding process was conducted at two different tube furnace temperatures: low (550Â Â°C) and high (1150Â Â°C), both for four hours. Microstructural and mechanical property evaluation of the low and high temperature nitrided low-carbon steel BS970-080A15 were studied and the results were compared to identify which gear had better performance in terms of hardness as well as corrosion resistance. The results from Vickers hardness test and weight loss analysis proved that high temperature nitrided carbon steel is harder and more corrosion resistant than the low temperature one. Â© 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim